Analisis Kelayakan Nasabah dalam Pembiayaan Akad Murabahah pada PT. BPRS XYZ (Jurnal Simki Economic, 2025)
This research aims to analyze the feasibility of customers in financing murabahah contracts at PT. SRB XYZ. The method used is a qualitative approach with descriptive research type. Data was collected through interviews with employees, direct observation, and documentation of funding applications for 2023. Analysis was carried out by applying the 5C principles (Character, Capacity, Capital, Collateral, Conditions) as well as triangulation techniques to ensure data validity. The research results show that customer eligibility analysis is carried out through several stages, such as document inspection, field survey, credit history analysis using BI Checking, and assessment of customer business capacity. Of the total 897 funding applications in 2023, 79% were successfully disbursed, while the rest were rejected or canceled due to data discrepancies, completeness of documents, and failure to meet financing criteria. This research concludes that implementing strict feasibility analysis procedures can minimize the risk of financing problems.